Racial discrimination and depression among on-reserve First Nations people in rural Saskatchewan - Janzen, Bonnie (Can J Public Health, 2017)
OBJECTIVES: To determine among rural-dwelling on-reserve Saskatchewan First Nations people whether racial discrimination is associated with depression, and in turn, if this relationship is moderated by gender. METHODS: As a component of a community-based participatory research project, a cross-sectional, interviewer-administered survey of 874 adults living on 2 Cree First Nation reserves in rural north-central Saskatchewan was conducted during May–August in 2012 and 2013. Self-reported, health-provider diagnosis of depression was the dependent variable and experiences of interpersonal racial discrimination was the primary exposure. Chi-square and multiple logistic regression were the main analytic techniques. Generalized estimating equations were applied to account for clustering within households. RESULTS: Overall, 64% of participants reported being treated unfairly in 1 or more situations because of their ethnicity; 38% indicated discrimination occurring in 3 or more situations. Nineteen percent reported a diagnosis of depression. Adjusted analyses indicated that compared to those with no experience of racial discrimination, those reporting 1–2 and 3 or more situations were 1.77 times (95% CI: 1.06–2.95) and 1.91 times (95% CI: 1.19–3.04) more likely to have diagnosed depression respectively. The relationship between racial discrimination and depression was not modified by gender, although women were 1.85 times (95% CI: 1.24–2.76) more likely to report depression than men. CONCLUSION: Interpersonal racial discrimination was associated with depression among First Nations women and men in rural Saskatchewan. Research directed at identifying the most efficacious interventions, programs and policies to combat racism is required to advance the goal of health equity.